Heat sink and preparation method thereof

By designing a laminated structure of the insulating thermal conductivity in the heat sink, the problem of insufficient thermal conductivity caused by low filling amount of boron nitride particles in the prior art is solved, and the thermal conductivity in the thickness direction is improved and the insulation maintenance is maintained.

CN114600567BActive Publication Date: 2025-04-25TEIJIN LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080077259.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-07
Filing Date
2020-11-06
Publication Date
2025-04-25
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

In the prior art, in the laminated body used to manufacture the heat sink, the filling amount of boron nitride particles is low, resulting in insufficient thermal conductivity in the thickness direction of the heat sink.

Method used

By designing a heat sink structure with at least two insulating heat conduction layers, the lamination direction of the insulating heat conduction layer is approximately orthogonal to the thickness direction of the heat sink, the insulating heat conduction layer contains 75 to 97% of the insulating particles, 3 to 25% of the binder resin, and a gap of less than 10% of the area in the cross-section.

Benefits of technology

The high thermal conductivity of the heat sink in the thickness direction is achieved, the thermal conductivity is 20W/(m·K) or above, and the insulation breakdown voltage is maintained at 5kV/mm or above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114600567B_ABST
    Figure CN114600567B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a heat sink having excellent thermal conductivity in the thickness direction. The solution is a heat sink having a structure in which at least two insulating thermally conductive layers are stacked, wherein the stacking direction of the insulating thermally conductive layers is substantially orthogonal to the thickness direction of the heat sink, wherein the insulating thermally conductive layers contain 75 to 97% by area of ​​insulating particles, 3 to 25% by area of ​​a binder resin, and 10% or less of voids in the entire cross section perpendicular to the surface direction of the heat sink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a heat sink and a method for producing the same, and more particularly to a heat sink that can effectively dissipate heat generated by semiconductor elements, power supplies, light sources, and other components used in electrical products and has electrical insulation properties and a method for producing the same. Background Art

[0002] A heat sink is a heat conducting member that is sandwiched between a heat source and a cooling material to release heat from the heat source to the cooling material, and is required to have high thermal conductivity in the thickness direction of the sheet. So far, studies have been conducted on obtaining a heat sink having high thermal conductivity in the thickness direction by cutting a laminate obtained by laminating primary sheets having high thermal conductivity in the in-plane direction into sheets along the lamination direction.

[0003] As an example of stacking and cutting a primary sheet having high thermal conductivity in the in-plane direction, there is an example in which ultra-high molecular weight polyethylene tapes and adhesive layers are alternately stacked and cut perpendicularly to the surface direction of the tapes to obtain a sheet having a thermal conductivity of 38 W / (m·K) in the thickness direction (Patent Document 1).

[0004] In addition, there is also an example of a sheet having a thermal conductivity of 27 W / (m·K) in the thickness direction obtained by stacking, pressing and cutting a primary sheet material obtained by filling 70 volume % of plate-like boron nitride powder in a mixture of an acrylic copolymer resin and a phosphate flame retardant (Patent Document 2). Patent Document 2 discloses that the plate-like boron nitride particles are oriented along their long axis direction relative to the thickness direction of the sheet.

[0005] In addition, there is an example of a sheet material having a thermal resistance of 0.25K / W in the thickness direction obtained by stacking, heating, pressing and vertically cutting a primary sheet material obtained by filling 65% by weight of plate-like boron nitride powder and 1.7% by weight of plate-like boron nitride agglomerated powder in a thermoplastic fluororesin (Patent Document 3). From this thermal resistance value and the shape of the sheet during measurement (1 cm×1 cm×0.30 mm), the thermal conductivity is estimated to be 12 W / mK.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-131705,

[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-222925,

[0010] Patent document 3: Japanese Patent Application Publication No. 2019-108496. Summary of the invention

[0011] Problems to be solved by the invention

[0012] In a conventional heat sink obtained by slicing a laminate in the lamination direction, the filling amount of boron nitride particles in the primary sheet material for producing the laminate is low, and the thermal conductivity in the thickness direction of the obtained heat sink may be insufficient.

[0013] The present invention has been made against the background of the above problems in the prior art. An object of the present invention is to provide a heat sink having excellent thermal conductivity in the thickness direction.

[0014] Means of solving problems

[0015] The inventors of this case have found that the above problems can be solved by the following methods:

[0016] <Method 1>

[0017] The heat sink has a structure formed by laminating at least two insulating and heat-conducting layers, wherein:

[0018] The stacking direction of the insulating heat-conducting layer is substantially orthogonal to the thickness direction of the heat sink.

[0019] The insulating heat-conductive layer contains 75 to 97 area % of insulating particles, 3 to 25 area % of binder resin, and less than 10 area % of voids in the entire cross section perpendicular to the surface direction of the heat sink;

[0020] <Method 2>

[0021] The heat sink according to embodiment 1, further comprising an insulating adhesive layer disposed between at least two of the insulating heat-conductive layers;

[0022] <Method 3>

[0023] The heat sink according to method 1 or 2, wherein the insulating thermally conductive layer occupies at least 50 volume % of the heat sink;

[0024] <Method 4>

[0025] The heat sink according to embodiment 2 or 3, wherein the thickness of the insulating thermal conductive layer in the stacking direction is at least twice the thickness of the insulating adhesive layer in the stacking direction;

[0026] <Method 5>

[0027] The heat sink according to any one of aspects 1 to 4, wherein the insulating particles include deformed flat particles;

[0028] <Method 6>

[0029] The heat sink according to any one of aspects 1 to 5, wherein the insulating particles contain 50% by volume or more of boron nitride particles;

[0030] <Method 7>

[0031] The heat sink according to any one of aspects 1 to 6, wherein the melting point or thermal decomposition temperature of the binder resin is 150° C. or higher;

[0032] <Method 8>

[0033] The heat sink according to any one of aspects 1 to 7, wherein the binder resin is an aromatic polyamide resin;

[0034] <Method 9>

[0035] The heat sink according to any one of aspects 1 to 8, wherein the thermal conductivity in the thickness direction is 20 W / (m·K) or more, and the insulation breakdown voltage is 5 kV / mm or more;

[0036] <Method 10>

[0037] The heat sink according to any one of aspects 1 to 9, wherein the relative dielectric constant at 1 GHz is 6 or less;

[0038] <Method 11>

[0039] A method for preparing a heat sink, which is the method for preparing a heat sink according to any one of methods 1 to 10, comprising:

[0040] Provide insulating thermal conductive sheet,

[0041] At least two of the insulating and thermally conductive sheets are stacked to obtain a stacked body, and

[0042] The heat sink is obtained by slicing the laminate along the approximate lamination direction of the insulating heat-conducting layer sheets.

[0043] Here,

[0044] The insulating thermally conductive sheet contains 75 to 97 area % of insulating particles, 3 to 25 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the insulating thermally conductive sheet;

[0045] <Method 12>

[0046] The method according to embodiment 11 further comprises disposing an insulating adhesive material between the insulating thermally conductive sheets when stacking at least two of the insulating thermally conductive sheets;

[0047] <Method 13>

[0048] The method according to embodiment 11 or 12, wherein the insulating thermally conductive sheet has a thermal conductivity of 30 W / (m·K) or more in the in-plane direction;

[0049] <Method 14>

[0050] The method according to any one of aspects 11 to 13, wherein the insulating particles include flat particles;

[0051] <Method 15>

[0052] The method according to any one of Methods 11 to 14, wherein the insulating particles contain 50% by volume or more of boron nitride particles.

[0053] Effects of the Invention

[0054] According to the present invention, a heat sink having excellent thermal conductivity in the thickness direction can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] [ Figure 1 ] Figure 1 A schematic diagram showing a cross section of a heat sink according to an embodiment of the present disclosure.

[0056] [ Figure 2 ] Figure 2 A schematic diagram showing a cross section of an insulating heat conductive layer constituting a heat sink according to an embodiment of the present disclosure.

[0057] [ Figure 3 ] Figure 3 A schematic diagram showing a cross section of an insulating heat conductive layer constituting a heat sink according to another embodiment of the present disclosure.

[0058] [ Figure 4 ] Figure 4 A schematic diagram showing a cross section of an insulating heat conductive layer constituting a heat sink according to the prior art.

[0059] [ Figure 5 ] Figure 5 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Example 1 is shown.

[0060] [ Figure 6 ] Figure 6 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Example 2 is shown.

[0061] [ Figure 7 ] Figure 7 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Example 3 is shown.

[0062] [ Figure 8 ] Figure 8 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Example 4 is shown.

[0063] [ Fig. 9 ] Fig. 9 A SEM image of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet precursor according to Reference Example 5 is shown.

[0064] [ Fig.10 ] Fig.10 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Comparative Example 1 is shown.

[0065] [ Fig.11 ] Fig.11 A SEM photograph of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet according to Reference Comparative Example 2 is shown. DETAILED DESCRIPTION

[0066] Hereinafter, embodiments of the present invention will be described.

[0067] Heat Sink

[0068] In the heat sink disclosed in the present invention,

[0069] The structure has at least two insulating and heat-conducting layers stacked together.

[0070] The stacking direction of the insulating thermal conductive layer is roughly orthogonal to the thickness direction of the heat sink.

[0071] The insulating thermally conductive layer contains 75 to 97 area % of insulating particles, 3 to 25 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the heat sink.

[0072] The heat sink of the present disclosure has a high filling rate of insulating particles and high thermal conductivity in the thickness direction.

[0073] Figure 1 A schematic diagram showing a cross section perpendicular to the surface direction of one embodiment of the heat sink involved in the present disclosure. Figure 1 As shown in FIG. 1 , in the heat sink 10, a plurality of insulating heat-conducting layers A are stacked, and the stacking direction is substantially orthogonal to the thickness direction of the heat sink. In the heat sink 10, an insulating adhesive layer B is disposed between each of the plurality of insulating heat-conducting layers A. Figure 1~Figure 4 , direction D represents the thickness direction of the heat sink, and direction S represents the in-plane direction of the heat sink.

[0074] In the heat sink of the present disclosure, an insulating thermally conductive sheet having high thermal conductivity in the in-plane direction is used as a material for the insulating thermally conductive layer. In the heat sink of the present disclosure, the stacking direction of such an insulating thermally conductive layer is substantially orthogonal to the thickness direction of the heat sink, thereby making the thermal conductivity in the thickness direction of the heat sink higher.

[0075] Here, in the present invention, "the stacking direction is approximately orthogonal to the thickness direction of the heat sink" means that the angle between the stacking direction and the thickness direction is 45°~135°, and preferably the angle is 55°~125°, 65°~115°, 75°~105°, 85°~95°, 87°~93° or 89°~91°.

[0076] In the heat sink of the present disclosure, the insulating heat conductive layer is preferably present in a manner that it exists continuously between one main surface and the other main surface of the heat sink and is exposed on one main surface and the other main surface. By existing in this manner, heat can be released from a component in contact with one surface of the heat sink to a component in contact with the other surface.

[0077] In another embodiment of the present disclosure, the insulating thermally conductive layer constituting the heat sink occupies at least 50% by volume of the heat sink. In this case, since the proportion of the insulating thermally conductive layer having higher thermal conductivity in the thickness direction increases, a heat sink having higher thermal conductivity in the thickness direction can be provided.

[0078] Preferably, the ratio of the insulating thermally conductive layer to the heat sink may be greater than 55 volume %, greater than 60 volume %, greater than 65 volume % or greater than 70 volume %, and / or may be less than 100 volume %, less than 100 volume %, less than 99 volume %, less than 98 volume %, less than 95 volume %, less than 90 volume %, less than 80 volume % or less than 75 volume %.

[0079] The thickness of the insulating heat-conductive layer can be set arbitrarily, but the thickness of the insulating heat-conductive layer can be 0.1 μm or more, 1 μm or more, or 10 μm or more, and / or can be 1000 μm or less, 100 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. The thickness of the insulating heat-conductive layer is, for example, 20 to 3000 μm, preferably 40 to 1000 μm.

[0080] The number of insulating thermally conductive layers contained in the heat sink can be arbitrarily set, for example, 3 layers or more, preferably 11 layers or more, and more preferably 21 layers or more. The upper limit of the number of insulating thermally conductive layers contained in the heat sink is not particularly limited, for example, it can be 1000 layers or less, 500 layers or less, 300 layers or less, or 100 layers or less.

[0081] The heat sink of the present disclosure may further include an insulating adhesive layer disposed between at least two insulating thermally conductive layers. By including the insulating adhesive layer between the insulating thermally conductive layers, the adhesion between adjacent insulating thermally conductive layers in the heat sink is further improved.

[0082] In one aspect of the heat sink according to the present disclosure, the heat sink further includes an insulating adhesive layer disposed between the insulating thermal conductive layers, whereby the insulating thermal conductive layers and the insulating adhesive layers are alternately stacked.

[0083] In the case where the heat sink also has an insulating adhesive layer, the greater the thickness of the insulating thermal conductive layer relative to the thickness of the insulating adhesive layer, the higher the thermal conductivity of the obtained heat sink in the thickness direction. Therefore, it is preferable that the thickness of the insulating thermal conductive layer is relatively thick. For example, the thickness of the insulating thermal conductive layer in the stacking direction is preferably more than twice the thickness of the insulating adhesive layer in the stacking direction. In this case, a heat sink with higher thermal conductivity in the thickness direction can be provided.

[0084] When the heat sink also has an insulating adhesive layer, the ratio of the thickness of the insulating thermal conductive layer in the stacking direction to the thickness of the insulating adhesive layer in the stacking direction may be greater than 2, greater than 3, greater than 4 or greater than 5, and / or may be less than 100, less than 80 or less than 50.

[0085] In the case where the heat sink also has an insulating adhesive layer, the thickness of each of the insulating thermal conductive layer and the insulating adhesive layer can be set arbitrarily, and can be 0.1 μm or more, 1 μm or more, or 10 μm or more, and / or can be 1000 μm or less, 100 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less, for example, 20 to 3000 μm, preferably 40 to 1000 μm, more preferably 0.5 to 500 μm, more preferably 5 to 50 μm, and particularly preferably 10 to 30 μm. The total of the insulating thermal conductive layer and the insulating adhesive layer can be set arbitrarily, for example, 3 layers or more, preferably 11 layers or more, and more preferably 21 layers or more. There is no particular upper limit on the total of the insulating thermal conductive layer and the insulating adhesive layer contained in the heat sink, for example, it can be 2000 layers or less, 1000 layers or less, or 500 layers or less.

[0086] <Thickness>

[0087] The thickness of the heat sink may vary depending on the heat source (eg, semiconductor element, power source, or light source) that the heat sink contacts when in use, and is, for example, 0.1 to 20 mm, preferably 0.5 to 5 mm.

[0088] <Thermal conductivity in thickness direction>

[0089] The heat sink according to the present disclosure preferably has a thermal conductivity of 20.0 W / (m·K) or more in the thickness direction.

[0090] In particular, the thermal conductivity of the heat sink in the thickness direction can be greater than 25.0 W / (m·K), greater than 30.0 W / (m·K), greater than 35.0 W / (m·K) or greater than 40.0 W / (m·K), and / or can be less than 60.0 W / (m·K), less than 50.0 W / (m·K) or less than 45.0 W / (m·K).

[0091] The thermal conductivity in the thickness direction of the heat sink can be calculated by multiplying the thermal diffusivity, specific gravity, and specific heat. That is, it can be calculated by the following formula:

[0092] (Thermal conductivity) = (thermal diffusivity) × (specific heat) × (specific gravity).

[0093] The thermal diffusivity in the thickness direction can be obtained by temperature wave analysis (temperature wave phase delay measurement method). The specific heat can be obtained by differential scanning calorimetry. In addition, the specific gravity can be obtained from the outer dimensions and weight of the insulating heat conductive layer.

[0094] <Thermal conductivity in the in-plane direction>

[0095] The heat sink of the present disclosure preferably has a thermal conductivity of 0.5 W / (m·K) or more in the in-plane direction. It is further preferred that the heat sink has a thermal conductivity of 1 W / (m·K) or more, 2 W / (m·K) or more, 5 W / (m·K) or more, or 10 W / (m·K) or more in the in-plane direction. The heat sink of the present disclosure preferably has a thermal conductivity of 100 W / (m·K) or less in the in-plane direction.

[0096] The thermal conductivity in the in-plane direction of the heat sink can be calculated by multiplying the thermal diffusivity, specific gravity, and specific heat. That is, it can be calculated by the following formula:

[0097] (Thermal conductivity) = (thermal diffusivity) × (specific heat) × (specific gravity).

[0098] The thermal diffusivity can be measured by the optical AC method using an optical AC thermal diffusivity measuring device. The specific heat can be obtained using a differential scanning calorimeter. In addition, the specific gravity can be obtained from the outer dimensions and weight of the insulating heat conductive layer.

[0099] <Dielectric Breakdown Voltage>

[0100] The heat sink preferably has a dielectric breakdown voltage of 5 kV / mm or more, 8 kV / mm or more, or 10 kV / mm or more. A dielectric breakdown voltage of 5 kV / mm or more is preferred because dielectric breakdown is less likely to occur and failure of electronic equipment can be avoided.

[0101] The insulation breakdown voltage of the heat sink can be measured according to the test standard ASTM D149. The measurement can be performed using a dielectric strength tester.

[0102] <Relative dielectric constant>

[0103] In one embodiment of the heat sink of the present disclosure, the relative dielectric constant at 1 GHz is not more than 6. When the relative dielectric constant of the heat sink at 1 GHz is not more than 6, interference of electromagnetic waves can be avoided, which is preferable.

[0104] The relative dielectric constant at 1 GHz is preferably 5.5 or less, 5.3 or less, 5.0 or less, or 4.8 or less. The lower limit of the relative dielectric constant is not particularly limited, and may be, for example, 1.5 or more or 2.0 or more.

[0105] The relative dielectric constant involved in the present disclosure can be measured using a network analyzer using a perturbation method and a closed cavity resonator method.

[0106] Hereinafter, each element constituting the heat sink of the present disclosure will be described in more detail.

[0107] <Insulating and thermally conductive layer>

[0108] The insulating heat-conductive layer disclosed herein contains, in the entire cross section perpendicular to the surface direction of the heat sink:

[0109] 75~97% by area of ​​insulating particles,

[0110] 3 to 25 area % of binder resin, and

[0111] Voids less than 10% by area.

[0112] The insulating heat-conductive layer of the present disclosure has high thermal conductivity in the in-plane direction. In the heat sink of the present disclosure formed by such an insulating heat-conductive layer, the lamination direction of the insulating heat-conductive layer is substantially orthogonal to the thickness direction of the heat sink, resulting in high thermal conductivity in the thickness direction of the heat sink. In addition, such an insulating heat-conductive layer has good flexibility, which is a preferred property from the perspective of, for example, mounting the heat sink on a semiconductor device.

[0113] Figure 2 A schematic cross-sectional view of the insulating thermally conductive layer A constituting the heat sink 10 according to the present disclosure is shown. In the insulating thermally conductive layer A, the filling rate of the insulating particles 21 becomes higher by reducing the content of the binder resin 22. It is believed that in the heat sink 10 composed of such an insulating thermally conductive layer A, since the filling rate of the insulating particles 21 is high, the distance between the particles becomes smaller, resulting in high thermal conductivity in the thickness direction D of the heat sink. In addition, it is believed that since the content of the binder resin 22 is reduced at the same time, the thermal resistance caused by the resin is suppressed.

[0114] In addition, Figure 2 In the insulating thermally conductive layer A, in addition to reducing the content of the binder resin 22, there are fewer voids 23 in the layer. It is believed that in the heat sink composed of such an insulating thermally conductive layer A, the filling rate of the insulating particles 21 is further increased, and the effect of increasing the thermal conductivity in the thickness direction D is further improved.

[0115] The insulating thermally conductive layer constituting the heat sink of the present disclosure is realized by, for example, using as a material an insulating thermally conductive sheet obtained by rolling a precursor of an insulating thermally conductive sheet containing insulating particles and a binder resin. The insulating thermally conductive sheet precursor formed into a sheet contains a large number of bubbles. It is believed that by compressing by rolling in this state, the insulating particles inside the sheet are oriented in the in-plane direction of the sheet, while the bubbles inside the insulating thermally conductive sheet precursor can be reduced, resulting in an increase in the thermal conductivity of the obtained insulating thermally conductive sheet in the in-plane direction.

[0116] Figure 4 A schematic cross-sectional view of an insulating heat conductive layer X constituting a heat sink according to the prior art is shown. In the insulating heat conductive layer X, the ratio of the binder resin 42 is high and the gaps 43 between the particles are large, so the filling rate of the insulating particles 41 becomes low. In the heat sink composed of such an insulating heat conductive layer X, it is considered that the distance between the insulating particles 41 is large, so that high thermal conductivity cannot be obtained in the thickness direction D.

[0117] It should be noted that the insulating thermally conductive layer is considered to have the same or substantially the same physical properties as the insulating thermally conductive sheet used as the insulating thermally conductive layer material when forming the heat sink, such as the same or substantially the same thermal conductivity and dielectric breakdown voltage. Therefore, regarding the physical properties of the insulating thermally conductive layer, namely the thermal conductivity, dielectric breakdown voltage and relative dielectric constant, reference can be made to the description of the insulating thermally conductive sheet described later.

[0118] <Insulating Particles>

[0119] The insulating thermally conductive layer according to the present disclosure contains insulating particles.

[0120] The insulating thermally conductive layer of the present disclosure contains 75 to 97 area % of insulating particles in the entire cross section perpendicular to the surface direction of the heat sink. When the content of the insulating particles is 75 area % or more, good thermal conductivity can be obtained, and when it is 97 area % or less, the viscosity increase of the resin composition can be suppressed, ensuring ease of molding.

[0121] Preferably, in the entire cross-section perpendicular to the surface direction of the heat sink, the insulating particles contained in the insulating thermally conductive layer involved in the present disclosure can be 80 area% or more, 85 area% or more, or 90 area% or more, and / or can be 96 area% or less, 95 area% or less, 94 area% or less, 93 area% or less, 92 area% or less, or 91 area% or less.

[0122] In the present disclosure, the "area %" of insulating particles in the entire cross-section perpendicular to the surface direction of the heat sink can be calculated by photographing the cross-section of the insulating thermal conductive layer perpendicular to the surface direction of the heat sink using a scanning electron microscope (SEM) and measuring the total area of ​​the insulating particles present in a certain area of ​​the obtained image.

[0123] The insulating particles are not particularly limited, and examples thereof include boron nitride, aluminum nitride, aluminum oxide, magnesium oxide, silicon nitride, silicon carbide, beryllium oxide, metal silicon particles with insulated surfaces, carbon fibers and graphite coated with insulating materials such as resins, and polymer fillers. From the viewpoint of thermal conductivity, insulation and price in the thickness direction of the heat sink, the insulating particles are preferably boron nitride particles, and particularly preferably hexagonal boron nitride particles. The aspect ratio of the boron nitride particles is preferably 10 to 1000, and more preferably has a flat shape.

[0124] The average particle size of the insulating particles is preferably 1 to 200 μm, more preferably 5 to 200 μm, further preferably 5 to 100 μm, and particularly preferably 10 to 100 μm.

[0125] The average particle size is the median diameter measured by the laser diffraction method using a laser diffraction / scattering particle size distribution measuring device (the particle size when a certain powder is divided into two parts at a certain particle size so that the particles larger than the particle size and the particles smaller than the particle size are equal, generally also called D50).

[0126] (Transformation)

[0127] In a favorable embodiment of the insulating and heat-conductive layer according to the present disclosure, the insulating particles include deformed flat particles, that is, scaly particles or flake particles.

[0128] In a heat sink having an insulating thermally conductive layer containing deformed flat particles, the thermal conductivity in the thickness direction is further improved. Although not intended to be limited by theory, the reason can be listed as follows: due to the deformation of the flat particles, the voids inside the insulating thermally conductive layer are further reduced. It is generally believed that in the case of flat particles, gaps are easily generated between particles due to steric hindrance caused by their shape. Therefore, it was previously believed that if the content rate of particles increases, the void ratio becomes larger. In contrast, in an insulating thermally conductive layer involved in a favorable embodiment of the present disclosure, for example, Figure 3 As shown in the insulating thermal conductive layer (A') shown in the figure, the flat particles 31 are deformed, so that the gaps between the particles are filled, and as a result, the voids 33 are further reduced. It is also believed that the flat particles 31 are deformed during the rolling process when the insulating thermal conductive sheet that becomes the material of the insulating thermal conductive layer is obtained, which promotes the discharge of the bubbles enclosed between the particles to the outside of the sheet, further promoting the reduction of the voids 33.

[0129] There is no particular limitation on the method for obtaining a heat sink having an insulating thermally conductive layer containing deformed flat particles. For example, there can be cited a method in which an insulating thermally conductive sheet is obtained by roll-pressing an insulating thermally conductive sheet precursor containing insulating particles containing flat particles, and using the insulating thermally conductive sheet to make a heat sink. In particular, it is believed that according to the method of roll-pressing an insulating thermally conductive sheet precursor in which the insulating particles contain flat particles and are highly filled with insulating particles, the deformation of the particles is more significant. Although it is not intended to be limited by theory, it is believed that in this method, the shear stress applied between the flat particles becomes higher, which results in the deformation of the flat particles being promoted. If Figure 3 The implementation method of is described as an example. Figure 3 In this state, the content of the binder resin 32 is low and the insulating particles are densely packed. It is considered that when the roll pressing process is performed in this state, since high shear stress is likely to act between the insulating particles, the insulating particles are particularly likely to deform.

[0130] It should be noted that in the conventional insulating thermal conductive layer, the insulating particles may be deformed. However, in this case, the degree of deformation is small and it is not considered to reduce the porosity.

[0131] When the insulating particles contain flat particles, the flat particles preferably account for 50% or more of the total insulating particles of 100% by volume. When the amount is 50% or more by volume, a good thermal conductivity in the in-plane direction can be ensured. The flat particles are more preferably 60% or more by volume, more preferably 70% or more by volume, more preferably 80% or more by volume, and particularly preferably 90% or more by volume relative to 100% by volume of the insulating particles.

[0132] (Flat particles)

[0133] Examples of the flat particles include hexagonal boron nitride (h-BN) particles.

[0134] The average particle size of the flat particles (especially boron nitride particles) is, for example, 1 μm or more, preferably 1 to 200 μm, more preferably 5 to 200 μm, more preferably 5 to 100 μm, and particularly preferably 10 to 100 μm. In the case of 1 μm or more, the specific surface area of ​​the flat particles is small, and compatibility with the resin can be ensured, so it is preferred; in the case of 200 μm or less, the uniformity of the thickness can be ensured during sheet molding, so it is preferred. Flat particles (especially boron nitride particles) can use flat particles with a single average particle size, or a mixture of a plurality of flat particles with different average particle sizes.

[0135] The aspect ratio of the flat particles is preferably 10 to 1000. When the aspect ratio is 10 or more, the orientation important for improving thermal diffusivity can be ensured, and high thermal diffusivity can be obtained, so it is preferred. In addition, fillers with an aspect ratio of 1000 or less can suppress the increase in the viscosity of the composition caused by the increase in specific surface area, and are preferred from the viewpoint of ease of processing.

[0136] The aspect ratio is the value obtained by dividing the major diameter of the particle by the thickness of the particle, that is, major diameter / thickness. When the particle is spherical, the aspect ratio is 1, and the aspect ratio increases as the degree of flatness increases.

[0137] The aspect ratio can be obtained by measuring the major axis and thickness of the particles at a magnification of 1500 times using a scanning electron microscope and calculating the major axis / thickness.

[0138] When using flat particles (particularly boron nitride particles) as insulating particles, insulating particles other than flat particles may also be used in combination. In this case, flat particles preferably account for more than 50% by volume relative to all insulating inorganic particles of 100% by volume. If more than 50% by volume, it is possible to ensure good thermal conductivity in the in-plane direction, therefore preferably. Relative to 100% by volume of insulating inorganic particles, flat particles are more preferably more than 60% by volume, more preferably more than 70% by volume, more preferably more than 80% by volume, and particularly preferably more than 90% by volume.

[0139] When flat particles and ceramic particles having isotropic thermal conductivity are used as insulating inorganic particles, the balance between the thermal conductivity in the thickness direction of the heat sink and the thermal conductivity in the in-plane direction of the heat sink can be adjusted as needed in the insulating thermal conductive layer, which is a preferred method. In addition, among flat particles, boron nitride particles are particularly expensive materials, so it is convenient to use them together with cheap materials such as metal silicon particles whose surfaces are insulated by thermal oxidation. In this case, the balance between the raw material cost and the thermal conductivity of the insulating thermal conductive layer can be adjusted as needed, which is a preferred method.

[0140] (Orientation)

[0141] From the viewpoint of obtaining particularly high thermal conductivity in the thickness direction of the heat sink, it is preferred that the insulating particles are oriented in the thickness direction of the heat sink so that the ratio of the thermal conductivity of the insulating thermally conductive layer in the thickness direction of the heat sink to the thermal conductivity of the insulating thermally conductive layer in the stacking direction exceeds 1. The ratio of the thermal conductivity of the insulating thermally conductive layer in the thickness direction of the heat sink to the thermal conductivity of the insulating thermally conductive layer in the stacking direction is preferably 1.5 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more. The ratio of the thermal conductivity of the insulating thermally conductive layer in the thickness direction of the heat sink to the thermal conductivity of the insulating thermally conductive layer in the stacking direction may be, for example, 500 or less, 200 or less, 100 or less, 50 or less, 30 or less, 20 or less, 15 or less, or 12 or less.

[0142] In the case of containing anisotropic flat particles having high thermal conductivity in the long axis direction such as hexagonal boron nitride particles as insulating particles, from the viewpoint of obtaining particularly high thermal conductivity in the thickness direction of the heat sink, it is preferred that the long axis direction of the anisotropic flat particles contained in the insulating heat conductive layer is substantially consistent with the thickness direction of the heat sink. It should be noted that "the two directions are substantially consistent" means that the angle formed by the two is, for example, 45° or less, preferably 30° or less, more preferably 15° or less, more preferably 5° or less or 3° or less, and particularly preferably 0°. In the case of containing flat boron nitride particles as insulating particles, from the viewpoint of obtaining high thermal conductivity in the thickness direction of the heat sink, it is particularly preferred that the boron nitride particles are oriented in a direction substantially parallel to the thickness direction of the heat sink.

[0143] Whether the major axis direction of the anisotropic flat particles contained in the insulating heat conductive layer substantially coincides with the thickness direction of the heat sink can be measured using a SEM image of the heat sink at a cross section perpendicular to the in-plane direction.

[0144] When the insulating thermally conductive layer contains boron nitride particles as insulating particles, the orientation degree of the boron nitride particles contained in the insulating thermally conductive layer is preferably less than 1. The lower the value of the orientation degree, the more the boron nitride particles are oriented in the same direction as the thickness direction of the heat sink. When the orientation degree of the boron nitride particles contained in the insulating thermally conductive layer is less than 1, the major axis direction of the boron nitride particles is oriented along the thickness direction of the heat sink, so that a higher thermal conductivity can be obtained in the thickness direction of the heat sink.

[0145] It should be noted that the orientation degree of the boron nitride particles in the insulating thermally conductive layer is considered to be substantially equal to the orientation degree of the boron nitride particles in the insulating thermally conductive sheet used when making the heat sink. Therefore, as the orientation degree of the boron nitride particles in the insulating thermally conductive layer, the orientation degree of the boron nitride particles in the insulating thermally conductive sheet described below can be used.

[0146] The orientation degree of the boron nitride particles in the insulating thermally conductive sheet used in making the heat sink is defined by the following formula using the (002) peak intensity I(002) corresponding to the c-axis (thickness) direction of the boron nitride particle crystals and the (100) peak intensity I(100) corresponding to the a-axis (plane) when measuring by transmission X-ray diffraction with the main surface of the insulating thermally conductive sheet as the measurement surface.

[0147] Orientation degree = I(002) / I(100).

[0148] The orientation degree of the boron nitride particles in the insulating thermally conductive layer is more preferably less than 0.8, less than 0.6, less than 0.4, less than 0.2 or less than 0.1, and particularly preferably substantially 0. The lower limit of the orientation degree of the boron nitride particles in the insulating thermally conductive layer is preferably 0 or more, 0.01 or more, or 0.1 or more.

[0149] <Binder Resin>

[0150] The insulating thermally conductive layer according to the present disclosure contains a binder resin.

[0151] The insulating heat-conductive layer involved in the present disclosure contains 3 to 25 area % of a binder resin in the entire cross section perpendicular to the surface direction of the heat sink. When the content of the binder resin is 25 area % or less, sufficiently high thermal conductivity can be ensured, and when it is 3 area % or more, moldability can be ensured. In addition, it is believed that when the content of the binder resin is 3 area % or more, the gaps between the insulating particles and the like are filled with the binder resin, and the voids can be reduced.

[0152] Preferably, in the entire cross section perpendicular to the surface direction of the heat sink, the binder resin contained in the insulating heat conductive layer of the present disclosure may be 5% by area or more, more than 5% by area, 6% by area or more, 7% by area or more, or 8% by area or more, and / or may be 24% by area or less, 20% by area or less, 15% by area or less, 12% by area or less, or 10% by area or less. In particular, it is believed that when the binder resin content is 5% by area or more, and in particular, more than 5% by area, a sufficient amount of binder resin for filling the gaps between insulating particles and the like can be ensured, and the voids can be further reduced.

[0153] In the present disclosure, the "area %" of the binder resin in the entire cross section perpendicular to the surface direction of the heat sink can be calculated by photographing the cross section perpendicular to the surface direction of the heat sink using a SEM and measuring the area of ​​the binder resin present in a certain area in the obtained image.

[0154] The binder resin involved in the present disclosure is not particularly limited. As the binder resin, for example, aromatic polyamide resin, polycarbonate resin, aliphatic polyamide resin, polyvinylidene fluoride (PVDF), silicone resin, polyimide resin, polytetrafluoroethylene (PTFE) resin, phenolic resin, epoxy resin, liquid crystal polymer (LCP) resin, polyarylate (PAR) resin, polyetherimide (PEI) resin, polyethersulfone (PES) resin, polyamideimide (PAI) resin, polyphenylene sulfide (PPS) resin, polyetheretherketone (PEEK) resin and polybenzoxazole (PBO) can be listed.

[0155] (Thermal Characteristics)

[0156] From the viewpoint of thermal properties of the insulating heat conductive layer, the binder resin preferably has excellent properties in terms of heat resistance and / or flame retardancy. In particular, the melting point or thermal decomposition temperature of the binder resin is preferably 150° C. or higher.

[0157] The melting point of the binder resin can be measured by a differential scanning calorimeter. The melting point of the binder resin is more preferably 200°C or higher, further preferably 250°C or higher, and particularly preferably 300°C or higher. The lower limit of the melting point of the binder resin is not particularly limited, and is, for example, 600°C or lower, 500°C or lower, or 400°C or lower.

[0158] The thermal decomposition temperature of the binder can be measured by a differential scanning calorimeter. The thermal decomposition temperature of the binder resin is more preferably 200°C or higher, further preferably 300°C or higher, particularly preferably 400°C or higher, and most preferably 500°C or higher. The lower limit of the thermal decomposition temperature of the binder resin is not particularly limited, and is, for example, 1000°C or lower, 900°C or lower, or 800°C or lower.

[0159] When used for heat dissipation inside vehicle-mounted electronic equipment, the resin material also needs to have a high heat resistance temperature. When using a power semiconductor made of silicon carbide, a heat resistance of about 300°C is required. Therefore, a resin having a heat resistance of more than 300°C can be suitably used for vehicle-mounted applications, especially for heat dissipation around power semiconductors. As such a resin, for example, an aromatic polyamide resin can be cited.

[0160] (Thermoplastic resin)

[0161] From the viewpoint of flexibility and handling, the binder resin is particularly preferably a thermoplastic binder resin. Since a heat sink composed of an insulating heat conductive layer containing a thermoplastic resin does not require thermal curing during preparation, it has excellent flexibility and can be easily applied to the interior of electronic equipment.

[0162] In addition, when the binder resin is a thermoplastic binder resin, it is believed that the voids in the insulating thermal conductive layer can be further reduced, which is particularly preferred. Although not intending to be limited by theory, when a thermoplastic resin is used as the binder resin, for example, by performing a heating treatment during the roll pressing process when preparing the insulating thermal conductive layer, it is believed that the thermoplastic resin softens, further promoting the discharge of bubbles trapped between the insulating particles, and as a result, the effect of reducing the voids can be further improved.

[0163] Examples of thermoplastic resins that can be used as the binder resin involved in the present disclosure include aromatic polyamide resins, polycarbonate resins, aliphatic polyamide resins, polyvinylidene fluoride (PVDF), thermoplastic polyimide resins, polytetrafluoroethylene (PTFE) resins, liquid crystal polymer (LCP) resins, polyarylate (PAR) resins, polyetherimide (PEI) resins, polyethersulfone (PES) resins, polyamideimide (PAI) resins, polyphenylene sulfide (PPS) resins, polyetheretherketone (PEEK) resins, and polybenzoxazole (PBO) resins.

[0164] (aramid resin)

[0165] It is particularly preferred that the binder resin is an aramid resin. When an aramid resin is used as the binder resin, an insulating heat-conducting layer having a higher mechanical strength can be obtained while filling insulating particles at a high ratio. In addition, from the viewpoint of thermal properties, it is also preferred that the binder resin is an aramid resin. Aramid resin has a relatively high thermal decomposition temperature, and a heat sink composed of an insulating heat-conducting layer using an aramid resin as a binder resin exhibits excellent flame retardancy.

[0166] Aramid resin is a linear polymer compound in which more than 60% of the amide bonds are directly bonded to aromatic rings. As the aramid resin, for example, poly(m-phenylene isophthalamide) and its copolymers, poly(p-phenylene terephthalamide) and its copolymers can be used, for example, copoly(p-phenylene·3,4'-diphenyl ether terephthalamide) (also known as copoly(p-phenylene·3,4'-oxydiphenyl terephthalamide) can be listed. Aramid resins can be used alone or in combination.

[0167] <Gap>

[0168] The insulating heat-conductive layer disclosed herein contains voids of 10% by area or less in the entire cross section perpendicular to the surface direction of the heat sink. When the voids are 10% by area or less, good thermal conductivity can be obtained in the thickness direction of the heat sink.

[0169] The insulating thermally conductive layer of the present disclosure preferably contains voids of 8% by area or less, 6% by area or less, 4% by area or less, 3% by area or less, 2% by area or less, or 1% by area or less in the entire cross section perpendicular to the surface direction of the heat sink. The lower limit of the voids is not particularly limited, for example, in the entire cross section perpendicular to the surface direction of the heat sink, the voids may be 0.01% by area or more, 0.1% by area or more, 0.5% by area or more, 0.8% by area or more, or 1.0% by area or more.

[0170] In the present disclosure, the "area %" of voids in the entire cross section perpendicular to the surface direction can be calculated by photographing a cross section of the insulating heat conductive layer perpendicular to the surface direction of the heat sink using a SEM and measuring the area of ​​voids existing in a certain area in the obtained image.

[0171] In the present disclosure, "voids" refer to gaps formed between elements constituting the insulating thermal conductive layer. The voids are generated, for example, when air bubbles or the like are trapped between insulating particles when forming the insulating thermal conductive layer.

[0172] <Volume Parts>

[0173] In another embodiment of the insulating thermally conductive layer of the present disclosure, the insulating thermally conductive layer of the present disclosure contains 75 to 97 parts by volume of insulating particles, 3 to 25 parts by volume of a binder resin, and 10 parts by volume or less of voids, based on 100 parts by volume of the insulating thermally conductive layer.

[0174] Preferably, the insulating particles contained in the insulating thermally conductive layer involved in the present disclosure may be 80 parts by volume or more, 85 parts by volume or more, or 90 parts by volume or more, and / or may be 96 parts by volume or less, 95 parts by volume or less, 94 parts by volume or less, 93 parts by volume or less, 92 parts by volume or less, or 91 parts by volume or less, relative to 100 parts by volume of the insulating thermally conductive layer.

[0175] Preferably, the binder resin contained in the insulating thermally conductive layer involved in the present disclosure may be more than 5 parts by volume, more than 6 parts by volume, more than 7 parts by volume, or more than 8 parts by volume relative to 100 parts by volume of the insulating thermally conductive layer, and / or may be less than 24 parts by volume, less than 20 parts by volume, less than 15 parts by volume, less than 12 parts by volume, or less than 10 parts by volume.

[0176] Preferably, the insulating thermally conductive layer of the present disclosure contains 8 parts by volume or less, 6 parts by volume or less, 4 parts by volume or less, 3 parts by volume or less, 2 parts by volume or less, or 1 part by volume or less of voids relative to 100 parts by volume of the insulating thermally conductive layer. The lower limit of the voids is not particularly limited, and for example, may be 0.01 parts by volume or more, 0.1 parts by volume or more, 0.5 parts by volume or more, 0.8 parts by volume or more, or 1.0 parts by volume or more.

[0177] When the insulating thermally conductive layer has a substantially uniform composition and thickness within the same sample surface, the area % of each component obtained from a cross section perpendicular to the surface direction is considered to be substantially equal to the volume ratio of each component in the insulating thermally conductive layer (volume fraction relative to 100 volume fractions of the insulating thermally conductive layer). Therefore, the volume fraction of voids in the insulating thermally conductive layer can be calculated in the same manner as described above with respect to the area % of voids.

[0178] <Additives>

[0179] The insulating heat-conducting layer of the present invention may contain a flame retardant, an anti-discoloration agent, a surfactant, a coupling agent, a colorant, a viscosity modifier and / or a reinforcing material. In addition, in order to improve the strength of the sheet, a fibrous reinforcing material may be contained. If short fibers of an aromatic polyamide resin are used as the fibrous reinforcing material, the heat resistance of the insulating heat-conducting layer will not be reduced due to the reinforcing material, so it is preferred.

[0180] <Insulating Adhesive Layer>

[0181] As a material of the insulating adhesive layer that may be included in the heat sink of the present disclosure, an insulating substance that can bond mutually adjacent insulating thermal conductive layers may be used, for example, a thermoplastic resin, a thermoplastic elastomer, or a cross-linking resin.

[0182] As the thermoplastic resin, for example, vinyl acetate resin, polyvinyl acetal, ethylene-vinyl acetate resin, vinyl chloride resin, acrylic resin, polyamide, cellulose, α-olefin, or polyester resin can be used.

[0183] As the thermoplastic elastomer, for example, chloroprene rubber, nitrile rubber, styrene-butadiene rubber, polysulfide rubber, butyl rubber, silicone rubber, acrylic rubber, polyurethane rubber, silylated polyurethane resin, and telechelic polyacrylate can be used.

[0184] Examples of the cross-linkable resin include epoxy resins, phenol resins, and polyurethane resins.

[0185] The insulating adhesive layer may contain additives such as a curing accelerator, an anti-discoloration agent, a surfactant, a coupling agent, a colorant, a viscosity modifier, and a filler, within a range that does not impair the insulating properties and the adhesive properties.

[0186] The insulating adhesive layer may have any form as long as it has adhesive strength, and may be in the form of a tape, a film, or a sheet, for example.

[0187] 《Preparation method》

[0188] The present disclosure includes a method for preparing the heat sink involved in the present disclosure, comprising the following steps:

[0189] Provide insulating thermal conductive sheet (providing process),

[0190] laminating at least two insulating thermally conductive sheets to obtain a laminate (laminating step), and

[0191] The heat sink is obtained by slicing the laminated body along the general lamination direction of the insulating thermally conductive sheets (slicing step);

[0192] Here, the insulating thermally conductive sheet contains 75 to 97 area % of insulating particles, 3 to 25 area % of the binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the insulating thermally conductive sheet.

[0193] <Providing process>

[0194] In the providing step involved in the method for preparing a heat sink involved in the present disclosure, an insulating thermally conductive sheet is provided, wherein the insulating thermally conductive sheet contains 75 to 97 area % of insulating particles, 3 to 25 area % of the above-mentioned binder resin, and less than 10 area % of voids in the entire cross-section perpendicular to the surface direction of the insulating thermally conductive sheet.

[0195] The thickness of the insulating thermally conductive sheet provided in the providing step is preferably 100 μm or less. The thickness of the insulating thermally conductive sheet is preferably 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less. There is no particular lower limit to the thickness of the insulating thermally conductive sheet, and for example, it may be 0.1 μm or more, 1 μm or more, or 10 μm or more.

[0196] (Thermal conductivity in the in-plane direction)

[0197] The thermal conductivity of the insulating thermally conductive sheet provided in the providing step is preferably 30 W / (m·K) or more, 35 W / (m·K) or more, 40 W / (m·K) or more, 45 W / (m·K) or more, 50 W / (m·K) or more, or 55 W / (m·K) or more in the in-plane direction. The higher the thermal conductivity of the insulating thermally conductive sheet provided in the providing step, the more preferred, but the generally achievable thermal conductivity in the in-plane direction is at most 100 W / (m·K).

[0198] (Thermal conductivity in thickness direction)

[0199] The thermal conductivity of the insulating thermally conductive sheet provided in the providing step is preferably 0.5 W / (m·K) or more and 5.0 W / (m·K) or less in the thickness direction. In particular, the thermal conductivity of the insulating thermally conductive sheet in the thickness direction may be 0.8 W / (m·K) or more or 1.0 W / (m·K) or more, and / or may be 4.5 W / (m·K) or less or 4.0 W / (m·K) or less.

[0200] (Dielectric Breakdown Voltage)

[0201] The insulation breakdown voltage of the insulating thermally conductive sheet provided in the providing step is preferably 5 kV / mm or more, particularly preferably 8 kV / mm or more or 10 kV / mm or more.

[0202] (Relative dielectric constant)

[0203] The relative dielectric constant of the insulating thermally conductive sheet provided in the providing step at 1 GHz is preferably 6 or less, particularly preferably 5.5 or less, 5.3 or less, 5.0 or less, or 4.8 or less. The lower limit of the relative dielectric constant is not particularly limited, and may be, for example, 1.5 or more or 2.0 or more.

[0204] From the viewpoint of obtaining particularly high thermal conductivity in the thickness direction of the heat sink, it is preferred that the insulating particles in the insulating thermally conductive sheet be oriented in the in-plane direction of the insulating thermally conductive sheet, so that the ratio of the thermal conductivity of the insulating thermally conductive sheet in the in-plane direction to the thermal conductivity of the insulating thermally conductive sheet in the thickness direction exceeds 1. The ratio of the thermal conductivity of the insulating thermally conductive sheet in the in-plane direction to the thermal conductivity of the insulating thermally conductive sheet in the thickness direction is preferably 1.5 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more. The ratio of the thermal conductivity of the insulating thermally conductive sheet in the in-plane direction to the thermal conductivity of the insulating thermally conductive sheet in the thickness direction may be, for example, 500 or less, 200 or less, 100 or less, 50 or less, 30 or less, 20 or less, 15 or less, or 12 or less.

[0205] When anisotropic flat particles having high thermal conductivity in the long axis direction, such as hexagonal boron nitride particles, are included as insulating particles, the long axis direction of the anisotropic flat particles in the insulating thermally conductive sheet is preferably substantially consistent with the in-plane direction of the insulating thermally conductive sheet from the viewpoint of obtaining particularly high thermal conductivity in the thickness direction of the heat sink. When flat boron nitride particles are included as insulating particles, it is particularly preferred that the boron nitride particles are oriented in a direction substantially parallel to the main surface of the insulating thermally conductive sheet from the viewpoint of obtaining high thermal conductivity in the thickness direction of the heat sink.

[0206] Whether the major axis direction of the anisotropic flat particles contained in the insulating thermally conductive sheet substantially coincides with the in-plane direction of the insulating thermally conductive sheet can be measured using a SEM image of the insulating thermally conductive sheet at a cross section perpendicular to the in-plane direction.

[0207] In the case where the insulating thermally conductive sheet contains boron nitride particles as insulating particles, the orientation degree of the boron nitride particles contained in the insulating thermally conductive sheet is preferably less than 1. The lower the value of the orientation degree, the more the boron nitride particles are oriented in the same direction as the in-plane direction of the insulating thermally conductive sheet. In the case where the orientation degree of the boron nitride particles contained in the insulating thermally conductive sheet is less than 1, since the long axis direction of the anisotropic flat particles is oriented along the in-plane direction of the insulating thermally conductive sheet, when a heat sink is prepared according to the preparation method disclosed in the present invention, a higher thermal conductivity can be obtained in the thickness direction of the heat sink.

[0208] The orientation degree of the boron nitride particles in the insulating thermally conductive sheet is defined by the following formula: the (002) peak intensity I(002) corresponding to the c-axis (thickness) direction of the boron nitride particle crystals and the (100) peak intensity I(100) corresponding to the a-axis (plane) when measured by transmission X-ray diffraction with the main surface of the insulating thermally conductive sheet as the measurement surface.

[0209] Orientation degree = I(002) / I(100).

[0210] The orientation degree of the boron nitride particles in the insulating thermally conductive sheet is more preferably less than 0.8, less than 0.6, less than 0.4, less than 0.2 or less than 0.1, and particularly preferably substantially 0. The lower limit of the orientation degree of the boron nitride particles in the insulating thermally conductive sheet is preferably 0 or more, 0.01 or more, or 0.1 or more.

[0211] (Method for preparing insulating thermally conductive sheet)

[0212] The insulating thermally conductive sheet involved in the present disclosure can be provided, for example, according to a method for preparing an insulating thermally conductive sheet having the following steps:

[0213] a mixing step of mixing insulating particles, a binder resin and a solvent to obtain a slurry,

[0214] a step of forming the slurry after the mixing step into a sheet shape and drying it to form an insulating thermally conductive sheet precursor, and

[0215] A roll pressing step of rolling the insulating thermally conductive sheet precursor.

[0216] (Mixing process)

[0217] In the mixing step of the method for producing an insulating thermally conductive sheet according to the present disclosure, insulating particles, a binder resin, and a solvent are mixed to obtain a slurry.

[0218] Regarding the insulating particles and the binder resin, the contents described above regarding the insulating thermal conductive layer can be referred to. The insulating particles preferably contain flat particles, and in particular contain 50% by volume or more of boron nitride particles relative to 100% by volume of the insulating particles. When the insulating particles contain boron nitride particles, the boron nitride particles are more preferably 60% by volume or more, further preferably 70% by volume or more, further more preferably 80% by volume or more, and particularly preferably 90% by volume or more relative to 100% by volume of the insulating inorganic particles.

[0219] In the mixing process, a flame retardant, an anti-discoloration agent, a surfactant, a coupling agent, a colorant, a viscosity modifier and / or a reinforcing material may be added arbitrarily. In order to increase the strength of the sheet, a fibrous reinforcing material may be added.

[0220] (Solvent)

[0221] As the solvent, a solvent capable of dissolving the binder resin may be used. For example, in the case of using an aromatic polyamide resin as the binder resin, 1-methyl-2-pyrrolidone, N,N-dimethylacetamide, or dimethyl sulfoxide may be used.

[0222] (mix)

[0223] The insulating particles, binder resin and solvent can be mixed using a general kneading device such as a paint shaker, a bead mill, a planetary mixer, a stirring disperser, a rotation and revolution stirring mixer, a three-roll mill, a kneader, a single-screw or double-screw kneading machine.

[0224] (Molding process)

[0225] In the molding step of the method for producing an insulating thermally conductive sheet according to the present disclosure, the slurry after the mixing step is formed into a sheet shape and dried to form an insulating thermally conductive sheet precursor.

[0226] (Shaping)

[0227] In order to form the slurry after the mixing step into a sheet, in addition to the method of applying the resin composition on a release film using a coater, a known method such as extrusion molding, injection molding, and lamination molding can be used.

[0228] (dry)

[0229] Drying can be performed by a known method. For example, the slurry coated on the substrate can be dried, and then the shaped slurry can be peeled off from the substrate in water and further dried. The drying temperature can be, for example, 50° C. to 120° C., and the drying time can be, for example, 10 minutes to 3 hours.

[0230] (Rolling process)

[0231] In the roll-pressing step of the method for producing an insulating thermally conductive sheet according to the present disclosure, an insulating thermally conductive sheet precursor is roll-pressed.

[0232] (Roller Pressing)

[0233] Rolling can be performed by a known method, for example, a calendering roller machine can be used to pressurize the insulating thermally conductive sheet precursor. The pressure provided to the insulating thermally conductive sheet precursor in the rolling process is preferably 400~8000N / cm in terms of linear pressure. By making the linear pressure above 400N / cm, the deformation of the insulating particles is easily caused, and the discharge of bubbles outside the sheet becomes significant. By making the linear pressure below 8000N / cm, the insulating particles are fully deformed and densely filled to a degree that they are not broken, and the gaps in the sheet can be reduced. The diameter of the roller used in the rolling is preferably 200~1500mm, for example.

[0234] (Heating temperature)

[0235] During the roll pressing process, the insulating thermally conductive sheet precursor is preferably heated. The heating temperature can be appropriately set according to the type of binder resin used. When an aromatic polyamide resin is used as the binder resin, the heating temperature is preferably 100 to 400°C. By setting the heating temperature to 100°C or higher, the binder resin is easily softened, and the effect of filling the gaps between the insulating particles is easily obtained by the roll pressing process. By setting the heating temperature to 400°C or lower, the strength of the binder resin is not easily reduced due to the thermal history.

[0236] (Flat particles)

[0237] In one embodiment of the preparation method involved in the present disclosure, the insulating particles contained in the slurry contain flat particles. In this case, it is believed that the voids in the sheet can be further reduced due to the deformation of the particles due to the rolling process. Although it is not intended to be limited by theory, it is believed that flat particles may be easily deformed compared to spherical particles, for example. In particular, it is preferred that the insulating particles contain more than 50% by volume of flat particles, especially boron nitride particles, relative to 100% by volume of the insulating particles. Relative to 100% by volume of the insulating particles, the flat particles, especially the boron nitride particles, are more preferably 60% by volume or more, further preferably 70% by volume or more, further more preferably 80% by volume or more, and particularly preferably 90% by volume or more.

[0238] In another embodiment of the method for preparing the insulating thermally conductive sheet involved in the present disclosure, the insulating particles contain flat particles, and the slurry contains 75 to 97 parts by volume of insulating particles and 3 to 25 parts by volume of binder resin relative to a total of 100 parts by volume of insulating particles and binder resin. In the case of rolling the insulating thermally conductive sheet precursor formed by such a slurry, it is believed that the voids in the insulating thermally conductive sheet are further reduced due to the further promotion of the deformation of the flat particles. Although it is not intended to be limited by theory, in the case where the content of the insulating particles in the insulating thermally conductive sheet precursor is high, the distance between the insulating particles is close, and the shear stress suffered by the insulating particles during rolling is high, which results in the deformation of the insulating particles being promoted. Moreover, since the flat insulating particles are deformed in a manner that fills the gaps in the sheet, it is believed that the void ratio in the sheet can be further reduced.

[0239] <Lamination process>

[0240] In the lamination step of the method for producing a heat sink according to the present disclosure, at least two insulating thermally conductive sheets are laminated to obtain a laminated body.

[0241] The lamination step can be performed by laminating a plurality of insulating thermally conductive sheets in the thickness direction. For example, a laminate can be obtained by laminating a plurality of insulating thermally conductive sheets cut into appropriate sizes.

[0242] In addition, the lamination process can be performed by folding or winding the insulating thermally conductive sheet. For example, the insulating thermally conductive sheet can be wound on the plate to form the first layer, and then a new layer can be wound on it to form the second layer. This operation is repeated until the desired number of layers is reached, thereby obtaining a laminate of insulating thermally conductive sheets. In addition, a plurality of laminates obtained in this way can be prepared and stacked to produce a laminate.

[0243] In the lamination process, after laminating the insulating thermally conductive sheets, heat treatment may be further performed. By further performing heat treatment, the adhesion between the insulating thermally conductive sheets in the obtained laminate is further improved. The temperature of the heat treatment may be appropriately set according to the type of binder resin contained in the insulating thermally conductive sheets, and is preferably a temperature that promotes fusion between the insulating thermally conductive sheets.

[0244] In the lamination process, when laminating the insulating thermally conductive sheets, a solvent may be applied to the insulating thermally conductive sheets. By applying the solvent to dissolve a portion of the binder resin constituting the insulating thermally conductive sheets, the adhesion between adjacent insulating thermally conductive sheets can be further improved. In this case, there is no particular limitation on the solvent, and a known solvent may be used depending on the type of binder resin contained in the insulating thermally conductive sheets.

[0245] (Insulating adhesive)

[0246] In the lamination step, when the insulating thermally conductive sheets are laminated, an insulating adhesive may be disposed between the insulating thermally conductive sheets.

[0247] In the lamination step, for example, when laminating insulating thermally conductive sheets, an insulating adhesive material is disposed between the insulating thermally conductive sheets, thereby obtaining a laminated body in which insulating conductive layers and insulating adhesive layers are alternately disposed.

[0248] When an insulating adhesive is disposed, the lamination step can be performed by repeatedly disposing the insulating adhesive on the surface of the insulating thermally conductive sheet by coating or pasting, and then laminating the insulating thermally conductive sheet thereon.

[0249] Alternatively, an insulating thermally conductive sheet may be wound on the plate to form the first layer, a substance constituting an insulating adhesive layer may be coated or adhered thereto, and then an insulating thermally conductive sheet may be wound thereon to form the second layer, and this operation may be repeated until the desired number of layers is reached, thereby performing a lamination process.

[0250] The insulating adhesive may be in any form such as liquid, powder or sheet. The insulating adhesive may be placed on the insulating thermally conductive sheet by any method such as coating, pasting, spraying, etc. For example, the insulating adhesive may be coated or sprayed in a layer. Alternatively, the insulating adhesive may be dissolved in a suitable solvent and then coated. In this case, the solvent may be selected appropriately according to the type of the insulating adhesive, and preferably hexane may be used.

[0251] Regarding the insulating adhesive material, reference may be made to the description regarding the above-mentioned insulating adhesive layer.

[0252] (suppress)

[0253] In the lamination step, the laminated body including at least two insulating thermally conductive sheets and any insulating adhesive material may be subjected to a pressing process.

[0254] The method of performing the pressing treatment is not particularly limited, and for example, hot pressing may be used. As hot pressing, for example, vacuum hot pressing using a vacuum hot press machine may be cited. The temperature of the hot pressing may be appropriately selected according to the binder resin and any insulating adhesive material constituting the insulating thermally conductive sheet. Hot pressing may be performed, for example, under vacuum conditions (for example, 0 to 10 Pa), at a temperature of 100°C to 300°C, and for 1 minute to 10 hours. Hot pressing may be performed, for example, under a pressurized condition of 0.1 to 1000 MPa, 0.2 to 500 MPa, 0.5 to 250 MPa, 1 to 100 MPa, 2 to 50 MPa, or 5 to 25 MPa.

[0255] <Slicing process>

[0256] In the slicing step of the method for producing a heat sink according to the present disclosure, the laminate is sliced ​​along the general lamination direction of the insulating thermally conductive sheets to obtain heat sinks.

[0257] The slicing process is performed so that the thickness direction of the heat sink obtained by slicing is substantially perpendicular to the stacking direction of the insulating and thermally conductive sheets constituting the heat sink.

[0258] The slicing process can be performed by a known method, for example, a multi-blade method, a laser processing method, a water jet method, a knife processing method, a fixed abrasive wire saw method, a free abrasive wire saw method, etc. In addition, the slicing process can be performed using, for example, a general knife or a cutting tool or a cutting machine such as a cutting knife, a razor, or a Thomson blade with a sharp blade. By using a cutting tool with a sharp blade or a fixed abrasive wire saw, etc., the disorder of the particle orientation near the surface of the heat sink obtained after the slicing process can be suppressed, and a heat sink with a thinner thickness can be easily obtained.

[0259] The thickness of the heat sink obtained by slicing is not particularly limited, and is, for example, 0.1 to 20 mm, preferably 0.5 to 5 mm. Example

[0260] Hereinafter, the invention according to the present disclosure will be described in more detail with reference to examples.

[0261] The measurement was performed by the following method.

[0262] (1) Thermal conductivity

[0263] The thermal conductivity in the thickness direction of the heat sink and the thermal conductivity in the in-plane direction of the insulating thermally conductive sheet are calculated by multiplying the thermal diffusivity, specific gravity, and specific heat.

[0264] (Thermal conductivity) = (Thermal diffusivity) × (Specific heat) × (Specific gravity)

[0265] The thermal diffusivity in the thickness direction of the heat sink was determined by the temperature wave analysis method. The measurement device used was ai-Phase mobile M3 type 1 manufactured by Ai-Phase. The thermal diffusivity in the in-plane direction of the insulating thermally conductive sheet was determined by the periodic heating radiation temperature measurement method. The measurement device used was LaserPIT manufactured by ADVANCE RIKO. The specific heat was determined using a differential scanning calorimeter (DSCQ10 manufactured by TAInstruments). The specific gravity was determined from the outer dimensions and weight of the heat sink and the insulating thermally conductive sheet.

[0266] (2) Insulation breakdown voltage

[0267] The dielectric breakdown voltage of the insulating sheet was measured in accordance with the test standard ASTM D 149. As the measuring device, a dielectric strength tester manufactured by Tokyo Transformer Co., Ltd. was used.

[0268] (3) Average particle size and aspect ratio

[0269] The average particle size of the boron nitride particles was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac BEL Corporation, MT3000) with a measurement time of 10 seconds and a measurement frequency of 1, and the D50 value in the volume distribution was obtained. The aspect ratio of the boron nitride particles was measured using a scanning electron microscope (Hitachi High-Technologies, TM3000 Miniscope) at a magnification of 1500 times, and the major diameter and thickness of the particles were measured and calculated.

[0270] 《Example 1》

[0271] <Preparation of heat sink>

[0272] (Preparation of Insulating Thermally Conductive Sheet)

[0273] In a state where 10 parts by volume of an aromatic polyamide resin "Technora" as a binder resin is dissolved, 90 parts by volume of plate-like boron nitride particles "PT110" (produced by Momentive, with an average particle size of 45 μm and an aspect ratio of 35) are added to 450 parts by volume of 1-methyl-2-pyrrolidone, and the mixture is mixed by stirring for 60 minutes with a Three-One Motor stirrer while heating to 80°C to obtain a uniform slurry.

[0274] The obtained slurry was coated on a glass plate using a bar coater with a gap of 0.35 mm to form a sheet, and dried at 70°C for 1 hour. Then, the shaped slurry was peeled off from the glass plate in water and dried at 100°C for 1 hour to obtain an insulating thermally conductive sheet precursor with a thickness of 120 μm. The obtained insulating thermally conductive sheet precursor was compressed using a calendering roller machine at a temperature of 270°C and a linear pressure of 4000 N / cm to obtain an insulating thermally conductive sheet with a thickness of 55 μm. The thermal conductivity of the insulating thermally conductive sheet in the in-plane direction is 40 W / (m·K).

[0275] (Layered)

[0276] The prepared insulating thermally conductive sheet was cut into pieces of 20 mm in length and 20 mm in width. The insulating thermally conductive sheet was alternately laminated with a layer formed by spraying a mixture of isohexane and cyclohexane in which styrene-butadiene rubber (SBR) was dissolved as an insulating adhesive layer. A laminate with a thickness of 28 mm was obtained by laminating a total of 400 insulating thermally conductive sheets. The thickness of the insulating adhesive layer was an average of 15 μm.

[0277] (cut off)

[0278] The produced laminate was cut twice with a razor blade at intervals of 1 mm substantially perpendicularly to the main surface of the insulating thermally conductive sheet to obtain a heat sink of 28 mm in length×20 mm in width×1 mm in thickness.

[0279] (Measurement)

[0280] The obtained heat sink had a thermal conductivity of 34 W / (m·K) in the thickness direction and a dielectric breakdown voltage of 12 kV.

[0281] 《Example 2》

[0282] <Preparation of heat sink>

[0283] (Preparation of Insulating Thermally Conductive Sheet)

[0284] 86 parts by volume of plate-like boron nitride particles "HSP" (produced by Dandong Chemical Engineering Institute Co., with an average particle size of 40 μm) were added to 450 parts by volume of 1-methyl-2-pyrrolidone in a state where 14 parts by volume of an aromatic polyamide resin "Technora" as a binder resin was dissolved, and the mixture was mixed by stirring for 60 minutes with a Three-One Motor stirrer while heating to 80°C to obtain a uniform slurry.

[0285] The obtained slurry was coated on a glass plate using a bar coater with a gap of 0.35 mm to form a sheet, and dried at 70°C for 1 hour. Then, the shaped slurry was peeled off from the glass plate in water and dried at 100°C for 1 hour to obtain an insulating thermally conductive sheet precursor with a thickness of 120 μm. The obtained insulating thermally conductive sheet precursor was compressed using a calendering roller machine at a temperature of 220°C and a linear pressure of 6000 N / cm to obtain an insulating thermally conductive sheet with a thickness of 50 μm. The thermal conductivity of the insulating thermally conductive sheet in the in-plane direction was 50 W / (m·K).

[0286] (Layered)

[0287] The prepared insulating thermally conductive sheet was cut into pieces of 100 mm in length and 100 mm in width. 100 groups (200 sheets) of the insulating thermally conductive sheet and the film-like hot melt adhesive "G-13" (manufactured by Kurabo Industries, Ltd., polyester, 30 μm thick) as the insulating adhesive layer were alternately laminated. After lamination, a vacuum hot press was used to maintain the temperature at 155°C, the pressure at 3 MPa, and the vacuum degree at 2 kPa for 5 minutes, thereby obtaining a laminate with a thickness of 8 mm.

[0288] (cut off)

[0289] The produced laminate was cut twice with a razor blade at intervals of 1 mm substantially perpendicularly to the main surface of the insulating thermally conductive sheet to obtain a heat sink of 100 mm in length×8 mm in width×1 mm in thickness.

[0290] (Measurement)

[0291] The thermal conductivity of the obtained heat sink in the thickness direction was 31 W / (m·K).

[0292] 《Reference Examples 1~5, Reference Comparative Examples 1~2》

[0293] Insulating thermally conductive sheets according to Reference Examples 1 to 4, insulating thermally conductive sheets according to Comparative Examples 1 to 2, and an insulating thermally conductive sheet precursor according to Reference Example 5 were prepared. The properties of the obtained insulating thermally conductive sheets and insulating thermally conductive sheet precursors were measured. The measurement was performed by the following method.

[0294] (1) Thermal conductivity

[0295] The thermal conductivity was calculated by multiplying the thermal diffusivity, specific gravity, and specific heat in the thickness direction and in the in-plane direction.

[0296] (Thermal conductivity) = (Thermal diffusivity) × (Specific heat) × (Specific gravity)

[0297] The thermal diffusivity in the thickness direction was determined by the temperature wave analysis method. The measuring device used was the ai-Phasemobile M3 type 1 manufactured by Ai-Phase. The thermal diffusivity in the in-plane direction was determined by the optical AC method. The measuring device used was the LaserPIT manufactured by ADVANCE RIKO. The specific heat was determined using a differential scanning calorimeter (DSCQ10 manufactured by TA Instruments). The specific gravity was determined from the outer dimensions and weight of the insulating sheet.

[0298] (2) Insulation breakdown voltage

[0299] The dielectric breakdown voltage was measured in accordance with the test standard ASTM D149. As the measuring device, a dielectric strength tester manufactured by Tokyo Transformer Co., Ltd. was used.

[0300] (3) Average particle size and aspect ratio

[0301] (i) The average particle size was measured using a laser diffraction / scattering particle size distribution measuring apparatus (MT3000 manufactured by Microtrac BEL Corporation) with a measurement time of 10 seconds and a measurement frequency of 1 time to obtain a D50 value in volume distribution.

[0302] (ii) Aspect Ratio The aspect ratio was determined by measuring the major axis and thickness of the particles at a magnification of 1500 times using a scanning electron microscope (TM3000 Miniscope manufactured by Hitachi High-Technologies) and calculating the aspect ratio.

[0303] (Bulk density)

[0304] For bulk density, the insulating thermally conductive sheet was cut into 50 mm squares, the mass was measured using a precision electronic balance, the thickness was measured using a micrometer, the sheet area was measured using a vernier caliper, and the result was obtained by calculation.

[0305] (Void ratio (area%))

[0306] The porosity was calculated from the area of ​​voids present in a certain area of ​​the obtained cross-sectional image by observing a cross section perpendicular to the surface direction at 300 times magnification using a scanning electron microscope (SEM).

[0307] (Orientation Degree)

[0308] The orientation degree of the boron nitride particles was evaluated by the peak intensity ratio of transmission X-ray diffraction (XRD, NANO-Viewer manufactured by Rigaku) ​​with the main surface of the insulating sheet as the measurement surface. The orientation degree was defined by the following formula using the (002) peak intensity I(002) corresponding to the c-axis (thickness) direction of the boron nitride crystal and the (100) peak intensity I(100) corresponding to the a-axis (plane).

[0309] (Orientation degree of boron nitride particles) = I(002) / I(100)

[0310] The lower the value of the orientation degree is, the more the boron nitride particles are oriented in the same direction as the in-plane of the sheet.

[0311] (Relative dielectric constant)

[0312] The relative dielectric constant of the insulating thermally conductive sheet at 1 GHz was measured using a network analyzer (E8361A manufactured by KEYCOM) using a perturbation method and a sample hole-enclosed cavity resonator method.

[0313] <Reference Example 1>

[0314] In the state where 5 parts by volume of the aromatic polyamide resin "Technora" (copolyparaphenylene 3,4'-diphenyl ether terephthalamide manufactured by Teijin Co., Ltd.) as a binder resin and 2 parts by volume of anhydrous calcium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a stabilizer for the dissolved resin are dissolved, 95 parts by volume of flaky boron nitride particles "HSL" (manufactured by Dandong Chemical Engineering Institute Co., with an average particle size of 30 μm) as insulating particles are added to 350 parts by volume of 1-methyl-2-pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and the mixture is mixed by stirring for 10 minutes with a rotation and revolution mixer to obtain a slurry. The obtained slurry is applied to a glass plate using a bar coater with a gap of 0.14 mm to form the slurry, and dried at 115°C for 20 minutes. Then, after immersion and desalination in ion exchange water for 1 hour, the slurry formed into a sheet is peeled off from the glass plate in water. The peeled sheet was dried at 100°C for 30 minutes to obtain an insulating thermally conductive sheet precursor with a thickness of 100 μm. The obtained insulating thermally conductive sheet precursor was compressed by a calender roll machine at a temperature of 280°C and a linear pressure of 4000 N / cm to obtain a soft insulating thermally conductive sheet with a thickness of 37 μm (the insulating thermally conductive sheet of Reference Example 1).

[0315] <Reference Example 2>

[0316] An insulating thermally conductive sheet having a thickness of 27 μm (insulating thermally conductive sheet of Reference Example 2) was obtained in the same manner as in Reference Example 1 except that the aramid resin was changed to 8 parts by volume and the flaky boron nitride particles were changed to 92 parts by volume.

[0317] <Reference Example 3>

[0318] In a state where 10 parts by volume of an aromatic polyamide resin "Technora" as a binder resin is dissolved, 90 parts by volume of flaky boron nitride particles "PT110" (produced by Momentive, with an average particle size of 45 μm and an aspect ratio of 35) as insulating particles are added to 450 parts by volume of 1-methyl-2-pyrrolidone (produced by Wako Pure Chemical Industries, Ltd.), and the mixture is mixed by stirring for 60 minutes with a Three-One Motor stirrer while heating to 80°C to obtain a uniform slurry.

[0319] The obtained slurry was coated on a glass plate using a bar coater with a gap of 0.28 mm to form a sheet, and dried at 70° C. for 1 hour. Then, the shaped slurry was peeled off from the glass plate in water and dried at 100° C. for 1 hour to obtain an insulating thermally conductive sheet precursor with a thickness of 100 μm. The obtained insulating thermally conductive sheet precursor was compressed using a calendering roll machine at a temperature of 270° C. and a linear pressure of 4000 N / cm to obtain an insulating thermally conductive sheet with a thickness of 48 μm (the insulating thermally conductive sheet of Reference Example 3).

[0320] <Reference Example 4>

[0321] An insulating thermally conductive sheet having a thickness of 25 μm (insulating thermally conductive sheet of Reference Example 4) was obtained in the same manner as in Reference Example 1 except that the aramid resin was changed to 20 parts by volume and the flaky boron nitride particles were changed to 80 parts by volume.

[0322] <Reference Comparative Example 1>

[0323] An insulating thermally conductive sheet precursor with a thickness of 100 μm was prepared by the same method as in Reference Example 1, except that the aromatic polyamide resin was set to 8 parts by volume and the flaky boron nitride particles were set to 92 parts by volume. Hot pressing was performed using a vacuum vertical hot press at 280°C and a vacuum atmosphere of 5 Pa with a load of 5 tons (20 MPa) for 2 minutes (the temperature was increased for 40 minutes after the start of pressing, maintained for 2 minutes, and then cooled for 70 minutes), thereby obtaining an insulating thermally conductive sheet with a thickness of 42 μm (refer to the insulating thermally conductive sheet of Comparative Example 1).

[0324] <Reference Comparative Example 2>

[0325] An insulating thermally conductive sheet having a thickness of 26 μm was obtained in the same manner as in Reference Example 1 except that the aramid resin was changed to 30 parts by volume and the flaky boron nitride particles were changed to 70 parts by volume (refer to the insulating thermally conductive sheet of Comparative Example 2).

[0326] <Reference Example 5>

[0327] The same method as in Reference Example 1 was followed except that the aramid resin was changed to 8 parts by volume and the flaky boron nitride particles were changed to 92 parts by volume, and drying was performed at 100° C. for 30 minutes to obtain an insulating thermally conductive sheet precursor having a thickness of 100 μm (Insulating thermally conductive sheet precursor of Reference Example 5).

[0328] 《Characteristics Evaluation》

[0329] The measurement results of Reference Examples 1 to 4, Comparative Examples 1 to 2, and Reference Example 5 are shown in Table 1. It should be noted that, for Reference Example 5, since the voids were large, it was not possible to define a cross section perpendicular to the plane direction, and evaluation at the cross section was not possible. Therefore, the area % of the insulating particles, binder resin, and void ratio of Reference Example 5 were recorded as "unable to measure".

[0330] [Table 1]

[0331]

[0332] As shown in Table 1, in the insulating thermally conductive sheets of Reference Examples 1 to 4, which contain 75 to 97 area % of insulating particles, 3 to 25 area % of binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the plane direction, a high thermal conductivity in the plane direction is observed. It should be noted that, as described above, the area % of the binder resin and the insulating particles substantially correspond to their volume parts, respectively, and in Table 1, "()" indicates such estimated area %.

[0333] In Reference Example 2, although the content of insulating particles is lower than that of Reference Example 1, the thermal conductivity in the in-plane direction is particularly high. One reason for such a result is that the porosity of Reference Example 2 is lower than that of Reference Example 1.

[0334] The insulating thermally conductive sheet of reference comparative example 1, which was subjected to vacuum hot pressing instead of roll pressing, contained 75 to 97 area % of insulating particles and 3 to 25 area % of binder resin in the entire cross-section perpendicular to the plane direction, while the porosity exceeded 10 area % and a low thermal conductivity was observed in the in-plane direction.

[0335] In the insulating thermally conductive sheet of Reference Comparative Example 2 in which the insulating particles accounted for less than 75 area % and the binder resin accounted for more than 25 area %, low thermal conductivity in the in-plane direction was also observed.

[0336] SEM Observation

[0337] The insulating thermally conductive sheets of Reference Examples 1 to 4, Reference Comparative Examples 1 to 2, and Reference Example 5 were observed using a scanning electron microscope (SEM).

[0338] Figure 5~Figure 8 SEM photographs of cross sections perpendicular to the surface direction of the insulating thermally conductive sheets of Reference Examples 1 to 4 are shown respectively. Figure 5~Figure 8 As shown, in the insulating thermally conductive sheets of Reference Examples 1 to 4, the flat boron nitride particles are deformed in a manner that fills the gaps in the sheet, for example, as compared with the case of Reference Comparative Example 1 that was subjected to vacuum hot pressing ( Fig.10 ) compared to the gap.

[0339] Fig. 9 FIG. 4 shows a SEM image of a cross section perpendicular to the surface direction of the insulating thermally conductive sheet precursor according to Reference Example 5. Fig. 9 As shown, in the sheet of Reference Example 5, which is an insulating thermally conductive sheet precursor that has not been subjected to a pressurization treatment, the voids are large and the filling degree of the insulating particles is low. In addition, no deformation of the flat insulating particles is observed.

[0340] Fig.10 FIG. 2 shows a SEM image of a cross section perpendicular to the surface direction of the sheet material involved in Reference Comparative Example 1. Fig.10 As shown in FIG. 1 , in the sheet of Reference Comparative Example 1, which was subjected to vacuum hot pressing without roller pressing during the pressurization treatment, the voids were reduced compared to Reference Example 5, which was not subjected to the pressurization treatment. However, due to the steric hindrance of the flat boron nitride particles, many voids remained in the insulating thermally conductive sheet. Fig.10 As shown, in the insulating thermally conductive sheet of Reference Comparative Example 1, although the flat insulating particles are deformed to a certain extent, the degree of deformation is insufficient to fill the gaps between the particles.

[0341] Fig.11 FIG. 2 shows a SEM image of a cross section perpendicular to the surface direction of the sheet material involved in Reference Comparative Example 2. Fig.11 As shown, in the sheet of Reference Comparative Example 2 in which the insulating particles account for less than 75 area % and the binder resin accounts for more than 25 area %, the distance between the insulating particles becomes larger due to the high content of the binder resin.

[0342] Reference Example 6 and Comparative Example 3

[0343] Next, a case where surface-insulated metal silicon particles were contained as insulating particles in addition to the boron nitride particles and an aromatic polyamide resin "Conex" (poly(m-phenylene isophthalamide) manufactured by Teijin Limited) was used as a binder resin was studied. Insulating thermally conductive sheets according to Reference Example 6 and Reference Comparative Example 3 were prepared and their physical properties were evaluated.

[0344] <Reference Example 6>

[0345] In a state where 20 parts by volume of aromatic polyamide resin "Conex" as a binder resin is dissolved, 60 parts by volume of flaky boron nitride particles "PT110" as insulating particles and 20 parts by volume of metal silicon particles "#350" (manufactured by KINSEI MATEC CO., LTD., with an average particle size of 15 μm and an aspect ratio of 1) whose surfaces are insulated by a thermal oxidation method (in the atmosphere, 900°C, for 1 hour) are added to 130 parts by volume of 1-methyl-2-pyrrolidone, and a scraper coater with a gap of 0.40 mm is used. Except for these two points, the same procedure as in Reference Example 3 is carried out to prepare an insulating thermally conductive sheet having a thickness of 56 μm (the insulating thermally conductive sheet of Reference Example 6) is obtained.

[0346] <Reference Comparative Example 3>

[0347] In a state where 40 parts by volume of an aromatic polyamide resin "Technora" as a binder resin is dissolved, 60 parts by volume of boron nitride particles "PT110" as insulating particles are added to 520 parts by volume of 1-methyl-2-pyrrolidone, and a scraper coater with a gap of 0.80 mm is used. Except for these two points, the same procedure as in Reference Example 3 is carried out to produce an insulating thermally conductive sheet having a thickness of 50 μm (refer to the insulating thermally conductive sheet of Comparative Example 3).

[0348] Table 2 shows the measurement results of Reference Example 6 and Reference Comparative Example 3.

[0349] [Table 2]

[0350] Table 2

[0351]

[0352] As shown in Table 2, in the insulating thermally conductive sheet of Reference Example 6, which contains 75 to 97 area % of insulating particles, 3 to 25 area % of binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the plane direction, a higher thermal conductivity in the in-plane direction is observed compared to the insulating thermally conductive sheet of Reference Comparative Example 3, which contains less than 75 area % of insulating particles and more than 25 area % of binder resin. In the insulating thermally conductive sheet of Reference Example 6, since it contains metal silicon particles in addition to boron nitride particles, the thermal conductivity in the thickness direction is improved compared to Reference Example 4.

[0353] Industrial Applicability

[0354] The heat sink of the present invention can be suitably used as an insulating heat dissipating member of a heat generating member of an electronic or electrical device, for example, can be suitably used as an insulating heat dissipating member for dissipating heat of a semiconductor to a cooling material or a frame.

[0355] Explanation of symbols

[0356] 10 heat sink,

[0357] 21, 31, 41 insulating particles,

[0358] 22, 32, 42 Binder resin,

[0359] 23, 33, 43 gaps,

[0360] A, A', X insulation and thermal conductive layer,

[0361] B Insulation adhesive layer,

[0362] D is the thickness direction of the heat sink,

[0363] S The face direction of the heat sink.

Claims

1. A heat sink having a structure formed by laminating at least two insulating and heat-conducting layers, wherein: The stacking direction of the insulating heat-conducting layer is substantially orthogonal to the thickness direction of the heat sink. The insulating heat-conductive layer contains 75 to 97 area % of insulating particles, 3 to 25 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the heat sink. The insulating particles include deformed flat particles.

2. The heat sink according to claim 1, wherein: The insulating heat conductive layer contains 80 to 97 area % of insulating particles, 3 to 20 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the heat sink.

3. The heat sink according to claim 1, wherein: The insulating particles do not contain aluminum nitride particles.

4. The heat sink according to claim 1 or 2, wherein: The flat particles contain boron nitride. 5 . The heat sink according to claim 1 , further comprising an insulating adhesive layer disposed between at least two of the insulating heat conductive layers.

6. The heat sink according to any one of claims 1 to 3, wherein: The insulating heat-conductive layer occupies at least 50 volume % of the heat sink.

7. The heat sink according to claim 5, wherein: The thickness of the insulating heat-conductive layer in the stacking direction is at least twice the thickness of the insulating adhesive layer in the stacking direction.

8. The heat sink according to any one of claims 1 to 3, wherein: The insulating particles contain 50% by volume or more of boron nitride particles.

9. The heat sink according to any one of claims 1 to 3, wherein: The melting point or thermal decomposition temperature of the binder resin is 150° C. or higher.

10. The heat sink according to any one of claims 1 to 3, wherein: The binder resin is an aromatic polyamide resin.

11. The heat sink according to any one of claims 1 to 3, wherein: The thermal conductivity in the thickness direction is 20 W / (m·K) or more, and the dielectric breakdown voltage is 5 kV / mm or more.

12. The heat sink according to any one of claims 1 to 3, wherein: The relative dielectric constant at 1 GHz is 6 or less.

13. A method for preparing a heat sink, which is the method for preparing a heat sink according to any one of claims 1 to 12, comprising: Provide insulating thermal conductive sheet, At least two of the insulating and thermally conductive sheets are stacked to obtain a stacked body, and Obtaining a heat sink by slicing the laminate along a general lamination direction of the insulating thermally conductive sheet; Here, The insulating thermally conductive sheet contains 75 to 97 area % of insulating particles, 3 to 25 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the insulating thermally conductive sheet. The insulating particles include deformed flat particles.

14. The method according to claim 13, wherein: The insulating heat conductive layer contains 80 to 97 area % of insulating particles, 3 to 20 area % of a binder resin, and 10 area % or less of voids in the entire cross section perpendicular to the surface direction of the heat sink. 15 . The method according to claim 13 , further comprising disposing an insulating adhesive material between the insulating thermally conductive sheets when stacking at least two of the insulating thermally conductive sheets.

16. The method according to claim 13 or 14, wherein: The insulating thermally conductive sheet has a thermal conductivity of 30 W / (m·K) or more in an in-plane direction.

17. The method according to claim 13 or 14, wherein: The insulating particles include flat particles.

18. The method according to claim 13 or 14, wherein: The insulating particles contain 50% by volume or more of boron nitride particles.

Citation Information

Patent Citations

  • Thermally conductive sheet, method for manufacturing the same and heat dissipating device using the same

    JP2016222925A

  • Thermal conductive sheet and production method thereof

    JP2019108496A

  • Thermally conductive sheet, method for producing same, and semiconductor device

    CN105283952A

  • Thermally conductive composite material

    CN108623840A

  • Insulating heat conductive sheet and manufacturing method thereof

    JP2019131705A